Conflict, food insecurity, and globalization - Messer, Ellen; Cohen, Marc J. (International Food Policy Research Institute, 2006)
We explore how globalization, broadly conceived to include international humanrights norms, humanitarianism, and alternative trade, might influence peaceful and foodsecure outlooks and outcomes. The paper draws on our previous work on conflict as a cause and effect of hunger and also looks at agricultural exports as war commodities. We review studies on the relationships between (1) conflict and food insecurity, (2) conflict and globalization, and (3) globalization and food insecurity. Next, we analyze countrylevel, historical contexts where export crops, such as coffee and cotton, have been implicated in triggering and perpetuating conflict. These cases suggest that it is not export cropping per se, but production and trade structures and food and financial policy contexts that determine peaceful or belligerent outcomes. Export cropping appears to contribute to conflict when fluctuating prices destabilize household and national incomes and when revenues fund hostilities. Also, in these scenarios, governments have not taken steps to progressively realize the right to adequate food or to reduce hunger and poverty. We conclude by exploring implications for agricultural development, trade, and human rights policies.